Analysis of the role of different intensity prevention and control measures in the current epidemic of novel coronavirus (2019-nCoV) infected pneumonia in Wuhan based on SIR model - Wen-Tao WU; Da-Ning LI; Li LI; Ao-Zi FENG; An-Ding XU; Jun LYU (Yixue xinzhi zazhi)
Since December 2019, a total of 6 neonates born to women with pneumonia suspected of new coronavirus (2019-nCoV) infection were admitted in our department. The gestational age and birth weights of the 6 neonates were 36 ± 3.4 weeks and 2.77 ± 0.66 kg, respectively. Three maternal patients were diagnosed with 2019-nCoV infected pneumonia, and 6 newborns were negative for coronavirus nucleic acid tests. Our department isolated and treated the 6 newborns according to patients with pneumonia suspected of 2019-nCoV infection. After active treatment, 1 of the children has been discharged, and 5 have stable vital signs. In order to prevent and control 2019-nCoV infection in neonatal intensive care unit effectively, we reported the caring details of the cases in the present study.